2018
DOI: 10.1016/j.jplph.2018.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Calcium ameliorates the toxicity of sulfate salinity in Brassica rapa

Abstract: Salinity stress in Brassica, often only associated with osmotic effects and the toxicity of Na, was more severe when applied as NaSO than as NaCl, indicating that SO ions had toxic effects as well. Application of 10 mM calcium in the form of CaCl in the growth medium of plants only slightly ameliorated growth impairment by NaCl and KCl, but almost completely prevented negative effects of NaSO and KSO on plant biomass production. This effect was calcium specific, as MgCl ameliorated sulfate toxicity to a much l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…5). As indicated earlier, sulphate salinity could reduce chelation and sequestration of Cr in roots (Reich et al 2015(Reich et al , 2018. Indeed, lower values of the S to Cr ratio in roots of rice seedlings treated with excessive rather than moderate S additions (Fig.…”
Section: Effect Of S Supply On Cr and S Uptake By Ricesupporting
confidence: 55%
See 1 more Smart Citation
“…5). As indicated earlier, sulphate salinity could reduce chelation and sequestration of Cr in roots (Reich et al 2015(Reich et al , 2018. Indeed, lower values of the S to Cr ratio in roots of rice seedlings treated with excessive rather than moderate S additions (Fig.…”
Section: Effect Of S Supply On Cr and S Uptake By Ricesupporting
confidence: 55%
“…S6). An increase in the growth inhibition of crop plants supplied with S in the form of sulphate has been reported to be associated with a substantial reduction of Ca, Mg, and Mn contents induced by salt stress in plant tissues at early growth stages (Reich et al 2018). Intriguingly, when rice plants were supplied with excessive S levels, Cr exposure not only did not impose any apparent stress, but also promoted rice growth (Fig.…”
Section: Treatmentsmentioning
confidence: 95%
“…Under salt stress, Ca 2+ content may be one of the important factors limiting crop growth; hence, management practices that replace Na + from cation exchange sites with Ca 2+ can ameliorate high Na + and its adverse effects (Bronick and Lal 2005). Adding an appropriate amount of Ca 2+ has been shown to be a beneficial approach for alleviating salt stress on plant growth caused by Na or sulfate (Tian et al 2015, Reich et al 2018). However, contrary results of Severino et al (2014) suggest that Ca does not alleviate the toxic effects of Na on the emergence and initial growth of castor, cotton, and safflower.…”
Section: Resultsmentioning
confidence: 99%
“…Some plant species such as wheat (Datta et al 1995), wild potato (Bilski et al 1988), barley (Huang and Redmann 1995), creeping screwbean (Reginato et al 2014), and cabbage (Paek et al 1988) were shown to be more susceptible to Na 2 SO 4 than to NaCl salinity. In Brassica rapa seedlings, sulfate salts (Na 2 SO 4 and K 2 SO 4 ) were more toxic than chloride salts (NaCl and KCl) (Reich et al 2016), and this toxicity is strongly ameliorated by calcium supplemented to the nutrient solution (Reich et al 2018). However there is still relatively little known about the mechanism of sulfate toxicity in plants.…”
Section: Introductionmentioning
confidence: 99%